The Climate Crisis : South African and Global Democratic Eco-Socialist Alternatives - Satgar, Vishwas; Satgar, Vishwas (Johannesburg Wits University Press, 2018)
Capitalism$1 (Bs addiction to fossil fuels is heating our planet at a pace and scale never before experienced. Extreme weather patterns, rising sea levels and accelerating feedback loops are a commonplace feature of our lives. The number of environmental refugees is increasing and several island states and low-lying countries are becoming vulnerable. Corporate-induced climate change has set us on an ecocidal path of species extinction. Governments and their international platforms such as the Paris Climate Agreement deliver too little, too late. Most states, including South Africa, continue on their carbon-intensive energy paths, with devastating results. Political leaders across the world are failing to provide systemic solutions to the climate crisis. This is the context in which we must ask ourselves: how can people and class agency change this destructive course of history? Volume three in the Democratic Marxism series, The Climate Crisis investigates eco-socialist alternatives that are emerging. It presents the thinking of leading climate justice activists, campaigners and social movements advancing systemic alternatives and developing bottom-up, just transitions to sustain life. Through a combination of theoretical and empirical work, the authors collectively examine the challenges and opportunities inherent in the current moment. This volume builds on the class-struggle focus of Volume 2 by placing ecological issues at the centre of democratic Marxism. Most importantly, it explores ways to renew historical socialism with democratic, eco-socialist alternatives to meet current challenges in South Africa and the world.s
English
Keywords: Climate change; Climate change; Capitalism; Democracy; South Africa